Optical coherence elastography of bilayer soft tissue based on harmonic surface wave spectroscopy. (October 2021) - Chen, Jinlong; Hu, Yongzheng; Lin, Xianglong; Liu, Haofei; Sun, Cuiru
Highlights: A new optical coherence elastography technique was developed based on harmonic mechanical excitation and surface wave spectroscopy (SWS). The OCT B-mode phase analysis mechanism proposed, enables the actual surface wave velocity calculation from the waveform observed by OCT imaging. The SWS model and the total variational regularization algorithm are proposed to solve the depth profile of the effective surface wave velocity, which is the key for accurate calculation of the elastic modulus of different layers. Abstract: Diseases often initiate from a certain layer of the biological tissue, thus simultaneous measurement of the elastic modulus of each layer is important for early diagnosis and treatment of various diseases. A surface wave spectroscopy (SWS) optical coherence elastography (OCE) technique based on harmonic wave excitation was proposed. An actuator consisting of a piezoelectric stack with a pin was designed to generate harmonic surface waves. A B-mode OCT data acquisition and phase analysis method was proposed to image the wave forms, and calculate the surface wave velocity. By exciting the sample with different frequencies, the surface wave dispersion curves were obtained. A total variation (TV) regularization iterative algorithm was proposed to obtain the elastic modulus distribution along the depth. Effectiveness of the proposed method was evaluated by both finite element simulation and experimental measurement of a bi-layer phantom. The mechanically driven harmonic wave actuation based OCE method is simple and cost-effective in experimental setup. Based on B-mode OCT scans, data analysis can be very fast, which is possible to realize real-time elastography imaging. This study provides an effective method for biomechanical properties study of layered tissue.